Market Rower; Banking and Financial Mediation: an Approach from the Industrial Organization - Jopen Sánchez, Guillermo (Economía, 2013)
This article provides an exploratory analysis of the process for determining intermediation margins in the Peruvian banking system. In the period between 2001 and 2010, this process was influenced primarily by two occurrences: the international financial crises towards the end of the 1990s, and the application of the Financial System Consolidation Program (Programa de Consolidación del Sistema Financiero) in Peru. The analysis delivers some evidence that in the case of Peruvian banking, market power and, specifically, the existence of market power-related inequalities between banks may be relevant factors in the process of determining financial intermediation margins.